Effect of Internal and External Investment on Economic Growth and Unemployment of Pakistan - Bukhari, Sara; Manzoor, Rimsha; Basharat, Usman (Minhaj International Journal of Economics and Organization Sciences, 2023)
This study focus on the impact of internal and external investments on unemployment rate and economic growth in Pakistan. The study uses data consist of the time span of 1984-2019.For the empirical estimation of the results, the Autoregressive Distributed Lags (ARDL) Model used for short-run and for long-run ARDL-Bound test approach use. The study’s empirical results suggest that internal investment increase the short-run as well as long-run GDP growth in Pakistan. Similarly, internal investment also decrees the long-run as well as short-run unemployment in Pakistan. On the other hand, the foreign investment have only short-run favorable impact on both Pakistan’s unemployment and economic growth. The short-run effect of foreign investment did not transmit into long-run because empirical evidence depicts the foreign investment’s insignificant impact on the unemployment rate and economic growth of Pakistan in long-run. The findings of the study ended with the policy measure and suggestions to channelize the effect of foreign and internal investment.